APLIKASI PERKONGRUENAN DALAM MENYELESAIKAN SISTEM PERSAMAAN LINEAR DUA PEUBAH - Yuni Yulida; Muhammad Ahsar Karim (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2009)
This paper discusses the determination of existention and solution of linearequation system with two variables written as:a x b y ca x b y ca x b y c    2 2 21 1 where x, y are integers, and n n n a ,a ,,a ,b ,b ,,b ,c ,c ,,c 1 2 1 2 1 2 are non-negativeintegers, using the application of linear congruency